2003
DOI: 10.1084/jem.20021806
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Signaling and Induction of Allergy-promoting Lymphokines Upon Weak Stimulation of the High Affinity IgE Receptor on Mast Cells

Abstract: Mast cell degranulation and de novo cytokine production is a consequence of antigen-aggregation of the immunoglobulin E (IgE)-occupied high affinity receptor for IgE (FcɛRI). Herein, we report that lymphokines that promote allergic inflammation, like MCP-1, were potently induced at low antigen (Ag) concentrations or at low receptor occupancy with IgE whereas some that down-regulate this response, like interleukin (IL)-10, required high receptor occupancy. Weak stimulation of mast cells caused minimal degranula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
124
1
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 133 publications
(136 citation statements)
references
References 55 publications
(63 reference statements)
10
124
1
1
Order By: Relevance
“…These data collectively argue that IL-4 and IL-10 alter the late phase mast cell response without affecting the early response. These results fit well with a recent report by Gonzalez-Espinosa and colleagues (64), demonstrating that mast cell degranulation requires greater Fc⑀RI signaling than does cytokine secretion. Following this theory, reduced Fc⑀RI expression after culture in IL-4 or IL-10 may force IgE receptor levels below the threshold needed for cytokine production without altering degranulation.…”
Section: Discussionsupporting
confidence: 92%
“…These data collectively argue that IL-4 and IL-10 alter the late phase mast cell response without affecting the early response. These results fit well with a recent report by Gonzalez-Espinosa and colleagues (64), demonstrating that mast cell degranulation requires greater Fc⑀RI signaling than does cytokine secretion. Following this theory, reduced Fc⑀RI expression after culture in IL-4 or IL-10 may force IgE receptor levels below the threshold needed for cytokine production without altering degranulation.…”
Section: Discussionsupporting
confidence: 92%
“…The lack of IL-10 expression seems to be a distinctive feature of H 2 O 2 -stimulated cells and can have important implications during the development of immune responses, since IL-10 has important suppressive activities and its absence in the microenvironment is relevant for T cell proliferation and subsequent cytokine production [31]. Recently, we observed a similar absence of IL-10 response when Fc 4 RI is weakly stimulated by low doses of Ag or low IgE occupancy of the receptor [32]. Weak stimulation of Fc 4 RI also primarily caused the production of chemokines, but IL-4 and IL-6 were two of few cytokines induced, thus providing evidence for the possible development of allergic inflammation in the absence of IL-10.…”
Section: Discussionmentioning
confidence: 65%
“…Although much is known about the role of Fc receptors (such as the high affinity receptor for IgE, Fc RI), TLRs, and a G protein-coupled receptors (2) on mast cell activation, the influence of the microenvironment in promoting mast cell responses is just beginning to be explored (3,4). Whether a stimulus induces mast cell granule exocytosis (5) and cytokine production or selectively induces just the latter has been demonstrated to be partly dependent on the strength of the stimulus (6,7). These studies showed that the cell's response is governed by kinetic proofreading parameters (molecular events) that must occur to achieve the particular response.…”
mentioning
confidence: 99%